Displays and breeding behaviour of the Chiloe Wigeon Anas sibilatrix - Brewer, Gwenda L (Wildfowl, 1996)
Many displays of the South American Chiloe Wigeon were similar to published displays of its close relatives, Eurasian and American Wigeon, Gadwall, and Falcated Duck, and differences appeared to be related to ecological and social factors. The loss of two courtship displays (Head-up-tail-up and Down-up) and the presence of an additional aggressive display (Wings-up) in all three wigeon species suggest that these features are related to their grazing lifestyle. Unlike the two northern wigeon, male Chiloe Wigeon have retained the Grunt-whistle display and did not perform Facing. Display bouts between male Chiloe Wigeon when their mates were incubating were interpreted as ritualized aggression, and some males directed courtship displays at other males in an aggressive context. Chiloe Wigeon actively maintained strong pairbonds through specialized Triumph Ceremonies, and males defended their mates vigorously, and usually successfully, during forced extra-pair copulation attempts. Both parents provided care for their ducklings and, from three days of age, ducklings directed displays to their parents and one another. These displays and family Triumph Ceremonies appeared to reinforce family bonds and encourage parental aggression towards other birds, showing convergence with geese and swans.